Management of subclavian artery in-stent restenosis. (December 2013) - Verma, Anil; Reilly, John P; White, Christopher J
Stenotic and occlusive diseases of the subclavian and brachiocephalic arteries can cause a significant morbidity as it can lead to symptomatic ischemia affecting the upper extremities, brain and, in some cases, the heart. An endovascular approach with primary stenting or provisional stenting has become the primary modality of revascularization of subclavian artery stenosis. In-stent restenosis can be treated with percutaneous transluminal angioplasty or repeat stenting and although stents offer superior long-term patency over balloon angioplasty alone for de novo lesions, there are no data regarding primary versus provisional stenting in subclavian in-stent restenosis. Here we describe a case of subclavian in-stent restenosis treated with just balloon angioplasty and demonstrate that provisional stenting with angioplasty alone when the percutaneous transluminal angioplasty results are excellent is a reasonable alternative to primary stent placement for subclavian in-stent restenosis.